Fragrance Contact Allergy - A Review Focusing on Patch Testing - Thanisorn Sukakul; Magnus Bruze; Cecilia Svedman (Medical Journals Sweden, 2024)
Fragrance materials are widely used in various types of products in daily life and many of them can be contact sensitizers. Contact allergy to fragrances has been reported to be common worldwide. Unlike other groups of contact allergens such as metals and preservatives, fragrance materials in consumer products can be present as single fragrance chemicals or in the form of mixtures known as natural complex substances. Due to the complexity of the fragrance materials and the high number of fragrance substances known to cause contact sensitization, selecting suitable materials for patch testing is challenging. Emerging fragrance markers have been additionally introduced in different baseline series for screening to enhance the rate of fragrance contact allergy detection. Moreover, there have been continual updates on basic knowledge, clinical perspectives, sources of exposure, and regulations on the use of fragrance materials. Avoiding pitfalls while performing patch testing with fragrance test materials is also crucial and should not be overlooked. Therefore, this review aims to update knowledge to provide a high-quality holistic approach to fragrance contact allergy diagnosis and management.